PENGARUH PROFESIONALISME, KOMITMEN ORGANISASI DAN SENSITIVITAS ETIKA TERHADAP INTENSI DALAM MELAKUKAN WHISTLEBLOWING - Linda Tanor; Ariaman Zega (JRAK: Journal of Accounting Research and Computerized Accounting, 2024)
The research aims to determine the effect of professionalism, organizational commitment, ethical sensitivity on intention to carry out whistleblowing. Respondents in this study were 51 employees of the Southeast Minahasa Inspectorate, North Sulawesi. This study uses primary data to obtain information from respondents using a purposive sampling method. The data processing method used is multiple regression analysis. The results of this study indicate that professionalism has no effect on the intention to take whistle-blowing action, organizational commitment has an effect on the intention to take whistle-blowing action, and ethical sensitivity has no effect on the intention to take whistle-blowing action.